2020
DOI: 10.1038/s41598-020-73523-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis uncovers the diagnostic value of miR-192-5p/HNF1A-AS1/VIL1 panel in cervical adenocarcinoma

Abstract: Despite the fact that the incidence of cervical squamous cell carcinoma has decreased, there is an increase in the incidence of cervical adenocarcinoma. However, our knowledge on cervical adenocarcinoma is largely unclear. Transcriptome sequencing was conducted to compare 4 cervical adenocarcinoma tissue samples with 4 normal cervical tissue samples. mRNA, lncRNA, and miRNA signatures were identified to discriminate cervical adenocarcinoma from normal cervix. The expression of VIL1, HNF1A-AS1, MIR194-2HG, SSTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
(49 reference statements)
0
15
1
Order By: Relevance
“…In our HeLa cell experiment, the main fragment was 61 nt, which indicates a unique fragment given that we had a maximum read length of 75 nt. Even though the methods used in Tong et al (25) and Xu et al (26, 27) were restricted to a maximum read length of 50 nt, we found traces of this fragment in the pile of fragments with unverifiable length of ≥ 50 nt. It must be emphasized, however, that we tried to validate the 5’ ETS rRF in yet another dataset, Snoek et al (62) (SRA accession: PRJNA413777), but here we failed to detect anything in the 5’ EST region.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…In our HeLa cell experiment, the main fragment was 61 nt, which indicates a unique fragment given that we had a maximum read length of 75 nt. Even though the methods used in Tong et al (25) and Xu et al (26, 27) were restricted to a maximum read length of 50 nt, we found traces of this fragment in the pile of fragments with unverifiable length of ≥ 50 nt. It must be emphasized, however, that we tried to validate the 5’ ETS rRF in yet another dataset, Snoek et al (62) (SRA accession: PRJNA413777), but here we failed to detect anything in the 5’ EST region.…”
Section: Discussioncontrasting
confidence: 53%
“…Despite only having read lengths of 50 nt to our disposal (see Results 7.1), where 5’ ETS rRF of Peak 1 was 61 nt, we found clear traces of this rRF (Figure 8J). Furthermore, to explore the clinical relevance of this finding we downloaded the Xu et al dataset (26, 27). Here sRNA was extract from confirmed cervical tumors and samples from normal cervix.…”
Section: Results and Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…To independently evaluate and define the LINC01016 gene structure, RNA-Seq datasets (20)(21)(22) were obtained, and splice events were determined based on de novo predictions for LINC01016 in the testis (Fig. 4A) and cervix (Fig.…”
Section: De Novo Prediction Of Splice Events Expression and Isoform Identification In Testis And Cervixmentioning
confidence: 99%